N-TUPLE ORBITS AND N-TUPLE WEAK ORBITS TENDING TO INFINITY - Mančevska, Sonja; Orovčanec, Marija (Matematichki Bilten, 2023)
In this paper we give a sufficient condition for \(n\) pairwise commuting and bounded linear operators on an infinite dimensional complex Banach space \(X\), which will imply that the space contains a dense set of vectors each with a corresponding \(n\)-tuple orbit tending to infinity. The same condition is sufficient to imply that the product of \(X\) and its dual space contains a dense set of pairs, each with a corresponding \(n\)-tuple weak orbit tending to infinity.